Impulsivity and Comorbid PTSD and Binge Drinking. Issue 2 (3rd April 2018) - Walker, Jesse; Bountress, Kaitlin E.; Calhoun, Casey D.; Metzger, Isha W.; Adams, Zachary; Amstadter, Ananda; Thomas, Suzanne; Danielson, Carla Kmett
Abstract: Objective: Trauma exposure is common, with estimates of 28% to 90% of adults reporting at least one traumatic event over their lifetime. Those exposed to traumatic events are at risk for alcohol misuse (i.e., binge drinking), posttraumatic stress disorder (PTSD), or both. A potential underlying mechanism for this comorbidity is increased impulsivity—the tendency to act rashly. Little work to date has examined the impact of different impulsogenic traits on this comorbidity.Methods: This study ( n = 162) investigated trauma-exposed young adults (aged 21–30) who had endorsed a lifetime interpersonal trauma. In addition, three impulsogenic traits (motor, nonplanning, and attentional) were measured.Results: Over and above the covariates for age, gender, race, and traumatic events, greater attentional impulsivity was associated with greater likelihood of meeting criteria for PTSD and binge drinking, compared to meeting criteria for PTSD, binge drinking, or neither. Neither nonplanning impulsivity nor motor impulsivity exerted unique effects.Conclusions: Young adults who report difficulty attending to immediate stimuli within their environment may be unable to think about and/or process the traumatic event, potentially increasing risk for PTSD and maladaptive coping skills to manage this distress (e.g., alcohol misuse, binge drinking).